Fatores associados à obesidade central em funcionários do campus saúde de uma Universidade Pública - Ana Luiza de Aquino (2014)
AQUINO, A. L. Factors associated with central obesity among employees of a health campus of Public University. 2014. 101 f. Dissertation (Master Degree in Nursing) Nursing School, Federal University of Minas Gerais, Belo Horizonte, 2014. Obesity has been recognized as a global epidemic and a serious public health problem, and its locate in the central region, also known as central obesity (CO) may increase the risk for developing type 2 diabetes, and is also constitute a predictor for cardiovascular disease. This is an epidemiological, cross-sectional and analytic study conducted in order to examine the factors associated with CO in employees of health campus of a public university. The sample consisted of 207 participants, of both sexes, aged between 18 and 60 years, whose demographic, socioeconomic, anthropometric, lifestyle and work conditions data were collected. The CO was defined according to the criteria proposed by NCEP-ATPIII, IDF and the measurement of WHR. It were done statistical analysis descriptive (absolute and relative frequencies), bivariate (chi-square test and Fisher's exact test) and multivariate analysis (Poisson regression) with significance level of 5% (p < 0.05). The prevalence of CO was 33.8% (95% CI: 27.4 to 40.7) NCEP-ATP III, 63.3% (95% CI: 56.3 to 69.8) IDF, and 29.0% (95% CI: 22.9 to 35.6) WHR. The anthropometric, biochemical, nutritional and lifestyle profiles of workers were very poor, with high prevalence of global obesity, dyslipidemia and hyperglycemia, inadequate dietary habits, and regular alcohol consumption. The female sex WHR (OR: 2.28, 95% CI 1.28 to 4.06), increasing age [NCEP-ATP III (PR: 1.04, 95% CI: 1.01-1.06); IDF (PR: 1.01, 95% CI 1.00 to 1.02); WHR (PR = 1.03, 95% CI: 1.01-1.05)] and physical activity [NCEP-ATP III = active (PR: 0.36, 95% CI 0.18 to 0.71); IDF = active (PR: 0.72, 95% CI 0.54 to 097); WHR = active (PR: 0, 27, 95% CI 0.11 to 0.66)] were independently associated with CO. It is important that these findings are considered in discussions on promoting worker health, aiming to establish measures for prevention, control and treatment of CO in this population and consequently decrease of chronic non-communicable diseases, emphasizing, especially, the regular physical practice.